Thrombotic events with or without thrombocytopenia in recipients of adenovirus-based COVID-19 vaccines - Cari, Luigi; Naghavi Alhosseini, Mahdieh; Bergamo, Alberta; Pacor, Sabrina; Pierno, Sabata; Sava, Gianni; Nocentini, Giuseppe (Frontiers in Cardiovascular Medicine, 2022)
COVID-19, the severe acute respiratory syndrome, is one of the major emergencies that have affected health care systems. Drugs and oxygen are only partially effective in saving lives in patients with severe COVID-19, and the most important protection from death is vaccination. The widespread use of COVID-19 adenovirus-based vaccines has provided evidence for the occurrence of rare venous thrombotic events including cerebral venous thrombosis and splanchnic venous thrombosis in recipients of Vaxzevria and Jcovden vaccines and the review focus on them. One year ago, thromboses in Vaxzevria recipients have been associated with thrombocytopenia in the presence of antibodies to platelet factor 4 and have been called vaccine-induced immune thrombotic thrombocytopenia (VITT). The incidence of VITT is equal to 9-31 events per one million doses of vaccines as evaluated by health agencies worldwide and is higher in female and young vaccine recipients. More recently, by using the European EudraVigilance database, it has been demonstrated that the incidence of thrombosis in recipients of adenovirus-based vaccines is 5-10 fold higher than that of VITT and 7-12 fold higher than observed in the recipients of Comirnaty, an mRNA-based vaccine, suggesting that adenovirus-based vaccines cause not only VITT but also thrombosis without thrombocytopenia (non-VITT thrombosis). The incidence of the vaccine-dependent non-VITT thrombosis is different in the adenovirus-based vaccines and the VITT/non-VITT incidence ratio depends on the severity of thrombosis and is inversely related to the age of the recipients. The possible causes and clinical implications of non-VITT thrombosis in vaccine recipients are discussed.